Defesa agropecuária e os serviços de inspeção: limites e possibilidades para geração de renda na agricultura familiar, um estudo de caso do serviço de inspeção do Maranhão e da região imediata de Viana/MA - Mesquita , Fabíola Ewerton Kamakura (2022)
Histórica! analysis of agricultura! defense, the State Inspectíon Service of Maranhão and the Municipal Inspection Services of the Immediate Geographic Region of Viana and its impacts for the income generation of family agriculture. It discusses in a synthetic way the construction of agricultura! defense in the country, presenting its priorities, contradictions and postural inheritances passed on to the other State structures of execution of this Public Policy, deepening in the analysis of the existing structure in the State of Maranhão and, even more specifically, in the State Inspection Service (S.LE) and its consequences for the rural population, with a priority focus for the small producer. It also includes an analysis of the current situation of the Municipal Inspection Services - S.I.M of the Immediate Geographic Region of Viana and the impact on small and family agroindustríes, as well as the consequences for the access of animal products to institutional markets, Food Acquisition Program - PAA and the Family Agriculture Purchase Program - PROCAF. It uses as methodology a historical analysis of the priority actions of agricultural defense, its contradictions and impacts, for this, bibliographic surveys and research were carried out in the documentation contained in the collection of the State Agency of Agricultura! Defense of Maranhão - AGED for collection of historical data and information, as well as reports and Information from the State Secretariai of Family Agriculture - SAF and the National Secretary for Social and Productive Inclusion (SEISP). Open interviews and the application of semi-structured questionnaires were also used as Instruments for data collection in the studied municipalities. It concludes that AGED, the executing body of the Agricultural Defense and Coordinator of the S.I.E. in Maranhão, had its actions strongly guided in the direction of making the State free of Foot-and-Mouth Disease, as well as assumed over the years a stance focused on directions dictated by the Ministry of Agriculture, which ied the actions of the Agricultural Defense to a reality that did not necessarily meet the demand of a large part of the State producers, especially family members, such as the hygienist posture adopted by the State Inspection Service - S.I.E, which despite having had changes with regard to the number of registered estabíishments and expansion of operations, still has great challenges, especially those related to small, artisanal and family agroindustries. It also concluded that in the Immediate Geographic Region of Viana, empirical clipping of the research, the challenge is greater with regard to the S.M S, since there is not, not even the legal framework of conception of the S.I.M in 80% of the citíes that make up the Region, due to the low understanding on the part of the Municipal Administrations of the negative consequences of such absence of these structures, not only for the health security of the population and the environment, but aíso for the promotion of the local economy, since this deficiency directly interferes in the verticaíization of the production of family farming